UTILITY PROFILE AT AUTOMOTIVE LABORATORY OF ENGINEERING FACULTY IN MAKASSAR STATE UNIVERSITY - S, Moh. Ahsan (Jurnal MEKANIKAL, 2011)
The aim of this research is to find out the utility profile of laboratory as the facility of student’s practical work in Automotive department, Engineering Faculty, Makassar State University. This research is a descriptive research. The population is the students of Automotive department in 2003, 2004, 2005 and 2006 Makassar State University. Sampling is taken randomly in amount of 70 people. The research variable data is collected by using questioner. The collected data is processed by using descriptive analysis with percentage. The output showed that the variable utility profile of laboratory with 3 sub variable, such as: 1). Utility pattern of devices and materials is in effective category of 67,4%, 2). Room layout pattern is in effective category of 61,4%, 3). Tutorial pattern of practical work lecturer is in effective category of 66,4%. After doing data analysis generally from the three aspects is obtained 66,01% or approriate with effective category.